Pengaruh Penambahan Minyak Terpentin pada Emisi Gas Buang Bahan Bakar Gasoline - Indah Mawarni, Drajat; Cahya Kusuma, Ardi (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2025)
This study evaluated the impact of using turpentine oil as an additive in gasoline fuel mixtures on exhaust emissions. Turpentine oil, obtained from pine tree resin, has flammable properties and high oxygen content, which is believed to be able to improve the combustion process in the engine. In this experiment, gasoline was mixed with turpentine oil in various concentrations (0%, 5%, 10%, 15% and 20%) and tested on a single-cylinder 4-stroke gasoline engine with engine speeds (1500, 3000, 4500 and 6000) rpm. The emissions analyzed included carbon monoxide (CO), hydrocarbons (HC), carbon dioxide (CO₂), and oxygen (O2). The results showed that the addition of turpentine oil in certain amounts could reduce CO and HC emissions at engine speeds above 4000 rpm due to more perfect combustion, although accompanied by a slight increase in CO2 and O2 emissions at engine speeds above 4000 rpm. Overall, turpentine oil shows potential as an environmentally friendly alternative additive in reducing emission pollution from gasoline fuel.